Vascularized 3D printed scaffolds for promoting bone regeneration. (January 2019) - Yan, Yufei; Chen, Hao; Zhang, Hongbo; Guo, Changjun; Yang, Kai; Chen, Kaizhe; Cheng, Ruoyu; Qian, Niandong; Sandler, Niklas; Zhang, Yu Shrike; Shen, Haokai; Qi, Jin; et al.
Abstract: 3D printed scaffolds hold promising perspective for bone tissue regeneration. Inspired by process of bone development stage, 3D printed scaffolds with rapid internal vascularization ability and robust osteoinduction bioactivity will be an ideal bone substitute for clinical use. Here, we fabricated a 3D printed biodegradable scaffold that can control release deferoxamine, via surface aminolysis and layer-by-layer assembly technique, which is essential for angiogenesis and osteogenesis and match to bone development and reconstruction. Our in vitro studies show that the scaffold significantly accelerates the vascular pattern formation of human umbilical endothelial cells, boosts the mineralized matrix production, and the expression of osteogenesis-related genes during osteogenic differentiation of mesenchymal stem cells. In vivo results show that deferoxamine promotes the vascular ingrowth and enhances the bone regeneration at the defect site in a rat large bone defect model. Moreover, this 3D-printed scaffold has excellent biocompatibility that is suitable for mesenchymal stem cells grow and differentiate and possess the appropriate mechanical property that is similar to natural cancellous bone. In summary, this 3D-printed scaffold holds huge potential for clinical translation in the treatment of segmental bone defect, due to its flexibility, economical friendly and practicality.